2018
DOI: 10.1111/aas.13222
|View full text |Cite
|
Sign up to set email alerts
|

Environmental safety: Air pollution while using MIRUS™ for short‐term sedation in the ICU

Abstract: Ambient room pollution was minimal in most cases, and the measured values were within or below the recommended exposure limits. Caution should be taken during refilling of the MIRUS™ system, as this was accompanied by higher pollution levels. The combined use of air-conditioning and gas scavenging systems is strongly recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Furthermore, devices to reduce atmospheric VA pollution must be considered. Studies have shown that an air-conditioning with at least six air changes per hour and a scavenging system should be used to reach mean VA concentrations below 1 ppm in the patient room (the National Institute of Occupational Safety and Health has defined an exposure limit of 2 ppm for ISO, SEVO, and DES in the air) [16, 17].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, devices to reduce atmospheric VA pollution must be considered. Studies have shown that an air-conditioning with at least six air changes per hour and a scavenging system should be used to reach mean VA concentrations below 1 ppm in the patient room (the National Institute of Occupational Safety and Health has defined an exposure limit of 2 ppm for ISO, SEVO, and DES in the air) [16, 17].…”
Section: Discussionmentioning
confidence: 99%
“…There are novel devices that have been added to classical ICU ventilators to administer inhaled anesthetics as sedatives, and thus a separate anesthesia machine is not necessary [59]. The effective collection and evacuation of the pollution to the outside atmosphere effectively ensures that the level of indoor contamination during the use of these new technologies remains below the recommended levels [61,62]. Still, careful planning of scavenging and ventilation systems is crucial to prevent excessive occupational exposure.…”
Section: Prevention Of Exposure To Wagsmentioning
confidence: 99%
“…at the exhalation outlet of the ventilator or at the oxygenator of the ECMO device. The exhalation outlet has the advantage that the gas flow can conduct viral particles and hence reduces the risk of infection for the health care personnel[ 34 , 35 ]. The oxygenator was used initially for intraoperative delivery of the anesthetic gas but modern reflection systems require containment of volatile anesthetics.…”
Section: Consumption Of Volatile Anesthetics In Covid-19 Related Ards Therapy Using Ecmomentioning
confidence: 99%
“…The CleanAir TM system (TIM, Koblenz, Germany) is recommended for gas flow conduction, because it is independent of the reflector (Figure 6 ). It operates well under vacuum, is sealed off the environment, and thus eliminates the risk of disseminating viral particles in the air[ 35 ].…”
Section: Hygiene Measures For Covid-19 Related Ardsmentioning
confidence: 99%
See 1 more Smart Citation